Optimal Study on Windproof Facilities Transition Section for Improving EMUs’ Operational Safety in Strong Wind Conditions - XU Jun; LIU Tanghong; LIANG Xifeng (机车电传动, 2017)
The safety of Lanzhou—Urumqi high-speed railway line, a high-speed railway through the strong wind area, affected with the strong wind environment seriously. Obvious shaking was found at some locations along the railway line during the full-scale test. Based on the field investigation and full-scale test, the three-dimensional, constant, incompressible and Reynolds average SST k-ω double equations were employed to simulate the flow field of one of the typical sections. The maximum velocity mutation points above the line were found and the original flow field was optimized by reconstruction of the local windbreak and shovelling method. It was found that the optimization results were satisfactory. In the case of 90° wind angle, at 3 m position above the 2# rail, the peak-to-peak lateral velocities of 1# transition, 1# ridge, 2# ridge, and 2# transition were 56.3%, 24.4%, 55.8% and 67.2% relative to that of original scheme, respectively